Androgen Deprivation Therapy for Prostatic Cancer in Patients With Torsades de Pointes - Lazzerini, Pietro Enea; Bertolozzi, Iacopo; Acampa, Maurizio; Cantara, Silvia; Castagna, Maria Grazia; Pieragnoli, Laura; D’Errico, Antonio; Rossi, Marco; Bisogno, Stefania; El-Sherif, Nabil; Boutjdir, Mohamed; Laghi-Pasini, Franco; et al. (Frontiers in Pharmacology, 2020)
Background. Men normally have shorter heart rate-corrected QT interval (QTc) than women, at least in part due to accelerating effects of testosterone on ventricular repolarization. Increasing data suggest that androgen-deprivation therapy (ADT) used for the treatment of prostatic cancer, may increase torsades de pointes (TdP) risk by prolonging QTc. However, the evidence for such an association is currently limited to few case reports, in most cases deriving from the analysis of uncontrolled sources such as pharmacovigilance databases. Objective. To better determine the clinical impact of ADT on TdP development, we examined the prevalence of this therapy in a consecutive cohort of 66 TdP patients, prospectively collected over a ~10 years period. Methods and Results. We found and described four patients who were under ADT for prostatic cancer when TdP occurred, in two cases degenerated to cardiac arrest. Notably, in this unselected population, ADTs unexpectedly represented the second most frequently administered QT-prolonging medication in males (4/24, 17%), after amiodarone. Moreover, in the ADT patients, a blood withdrawal was performed within 24h from TdP/marked QTc prolongation occurrence and circulating concentration of androgens and gonadothropins were measured. As expected, all cases showed markedly reduced testosterone levels (total, free, and available). Conclusion. We provide evidence that a significant proportion of patients developing TdP were under treatment with ADT for prostatic cancer, thus confirming the clinical relevance of previous pharmacovigilance signals. An accurate assessment of the arrhythmic risk profile should be included in the standard of care of prostatic cancer patients before starting ADT.